1999
DOI: 10.1097/00019606-199906000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Test for Identification of a Human Papillomavirus 16 E6 L83V Variant

Abstract: A variant of human papillomavirus (HPV) 16 has been shown recently to be more prevalent in invasive cervical carcinoma than in preinvasive lesions. This HPV 16 variant possesses a common mutation (T to G) in nucleotide 350 (codon 83) of the E6 gene, resulting in an amino acid shift, L83V, in the E6 protein. This mutation was believed to signify preinvasive cervical lesions with a high probability of progression to invasive carcinoma. The purpose of the present investigation is to describe a rapid method for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…To distinguish monoclonal PCR products from polyclonal, single-stranded conformation polymorphism (SSCP), analysis was performed as reported elsewhere (18). In one case for which a clonal PCR product was lacking in the diagnostic tumor (Case 33), further analyses were carried out using Southern blotting and hybridization with a J H probe to determine clonality of the IGH gene as previously detailed (19).…”
Section: Analyses Of Clonal Relationshipmentioning
confidence: 99%
“…To distinguish monoclonal PCR products from polyclonal, single-stranded conformation polymorphism (SSCP), analysis was performed as reported elsewhere (18). In one case for which a clonal PCR product was lacking in the diagnostic tumor (Case 33), further analyses were carried out using Southern blotting and hybridization with a J H probe to determine clonality of the IGH gene as previously detailed (19).…”
Section: Analyses Of Clonal Relationshipmentioning
confidence: 99%
“…The PCR product was run on a SSCP gel and a polymorphism of E6 codon 83 was identified after silver staining by discrepant band pattern of the two sequence variants. The method has been described in detail before (Alemi et al, 1999). The primer pairs used for the HPV analyses are specified in Table 1.…”
Section: Hpv-testingmentioning
confidence: 99%
“…In the present investigation, a collection of invasive cervical adenocarcinomas infected with HPV16 was analysed for the presence of a point mutation in codon 83 of the E6 gene, by a novel, rapid, PCR-based method (Alemi et al, 1999). It was observed that the HPV16 E6 variant was more predominant in the invasive squamous lesions than in the adenocarcinomas.…”
mentioning
confidence: 91%
“…2 Recently, it has also been used for studies of viral evolution and molecular epidemiology. 6,42 As described for other systems, both types of gels, with and without glycerol, were necessary for detection of all substitutions.…”
Section: Discussionmentioning
confidence: 99%